High-speed visualization of acoustically excited cavitation bubbles in a cluster near a rigid boundary - Vaidya, Haresh Anant; Ertunc, Özgür; Lichtenegger, Thomas; Hachmann, Johannes; Delgado, Antonio; Skupin, Andreas (Journal of Visualization, 2015)
Abstract: In the present work, high-speed visualizations at one million frames/s have been used to study the oscillation characteristics of acoustic cavitation bubbles. The bubbles are generated by acoustic cavitation using an ultrasound transducer with an excitation frequency of 75 kHz near a rigid surface and the medium used is deionized water. The cavitation bubbles tend to collect in clusters near solid boundaries, where they are visualized using a high-speed camera. The collective oscillations give rise to many interesting phenomena like bubble collapse, coalescence, fragmentation and bubble translation. The image sequences provided here contribute to the better understanding of the entire lifecycle of acoustic cavitation bubbles.
UnivIS-Import:2015-04-02:Pub.2015.tech.ITC.stmmec.highsp
Keywords: Acoustic cavitation; Bubble cluster; Bubble dynamics; High-speed visualizations; Ultrasound

High speed visualization of acoustic cavitation bubble dynamics near a rigid surface - Vaidya, Haresh Anant; Ertunc, Özgür; Skupin, Andreas; Delgado, Antonio (Proceedings der 21. GALA-Fachtagung "Lasermethoden in der Strömungsmesstechnik", 2013)
UnivIS-Import:2015-04-16:Pub.2013.tech.ITC.stmmec.highsp

Numerical simulations of swirling pipe flows - decay of swirl and occurrence of vortex structures - Vaidya, Haresh Anant; Ertunc, Özgür; Genc, Balkan; Beyer, Florian; Köksoy, Cagatay; Delgado, Antonio (Journal of Physics : Conference Series, 2011)
The present work aims at better understanding of the physics underlying swirling flows in pipes by means of numerical simulations. Direct numerical simulations have been carried out by using two different inlet swirl conditions. In one case, rotating honeycomb is used as the means to generate swirl whereas in the other case a solid body rotation is provided at the inlet. The inlet swirl intensity is varied in order to scan the underlying physics. Reynolds number 1730 is selected so that the flow remains in laminar regime. The results are compared with those obtained from the experiments using a similar experimental set-up. It is shown that the increase in the inlet swirl intensity leads to a faster decay of swirl downstream of the pipe. Similarly certain specific vortex structures are observed in the radial velocity contours. These structures are thought to be analogous with those found in the Taylor-Couette flow between a stationary outer cylinder and inner rotating cone. The reported investigations reveal dependence of swirl decay on the inlet swirl intensity and occurrence of vortex structure

Numerical simulations of swirling pipe flows- decay of swirl and occurrence of vortex structures - Vaidya, Haresh Anant; Ertunc, Özgür; Genc, Balkan; Köksoy, Cagatay; Beyer, Florian; Delgado, Antonio (Journal of Physics : Conference Series, 2011)
The present work aims at better understanding of the physics underlying swirling flows in pipes by means of numerical simulations. Direct numerical simulations have been carried out by using two different inlet swirl conditions. In one case, rotating honeycomb is used as the means to generate swirl whereas in the other case a solid body rotation is provided at the inlet. The inlet swirl intensity is varied in order to scan the underlying physics. Reynolds number 1730 is selected so that the flow remains in laminar regime. The results are compared with those obtained from the experiments using a similar experimental set-up. It is shown that the increase in the inlet swirl intensity leads to a faster decay of swirl downstream of the pipe. Similarly certain specific vortex structures are observed in the radial velocity contours. These structures are thought to be analogous with those found in the Taylor-Couette flow between a stationary outer cylinder and inner rotating cone. The reported investigations reveal dependence of swirl decay on the inlet swirl intensity and occurrence of vortex structures.
UnivIS-Import:2015-04-14:Pub.2011.tech.ITC.stmmec.numeri_5

The penetration of acoustic cavitation bubbles into micrometer-scale cavities - Vaidya, Haresh Anant; Ertunc, Özgür; Lichtenegger, Thomas; Delgado, Antonio; Skupin, Andreas (Ultrasonics, 2015)
The penetration of acoustically induced cavitation bubbles in micrometer-scale cavities is investigated experimentally by means of high-speed photography and acoustic measurements. Micrometer-scale cavities of different dimensions (width = 40. μm, 80. μm, 10. mm and depth = 50. μm) are designed to replicate the cross section of microvias in a PCB. The aim here is to present a method for enhancing mass transfer due to the penetration of bubbles in such narrow geometries under the action of ultrasound. The micrometer-scale cavities are placed in a test-cell filled with water and subjected to an ultrasound excitation at 75. kHz. A cavitation bubble cluster is generated at the mouth of the cavity which acts as a continuous source of bubbles that penetrate into the cavity. The radial oscillation characteristics and translation of these bubbles are investigated in detail here. It is observed that the bubbles arrange themselves into streamer-like structures inside the cavity. Parameters such as bubble population and size distribution and their correlation with the phase of the incident ultrasound radiation are investigated in detail here. This provides a valuable insight into the dynamics of bubbles in narrow confined spaces. Mass transfer investigations show that fresh liquid can be continuously introduced in the cavities under the action of ultrasound. Our findings may have important consequences in optimizing the filling processes for microvias with high aspect ratios.
UnivIS-Import:2016-02-10:Pub.2015.tech.ITC.stmmec.thepen
Keywords: Acoustic cavitation; Bubble dynamics; Mass transfer; Microvias; Ultrasound

Untersuchung des Einflusses von Tensiden (oberflächenaktive Stoffe) auf die Dynamik der akustischen Kavitationsblasen in Wandnähe mithilfe von Hochgeschwindigkeitsaufnahmen - Vaidya, Haresh Anant; Ertunc, Özgür; Delgado, Antonio; Hachmann, Johannes; Lichtenegger, Thomas (Proceedings der 22. GALA-Fachtagung "Lasermethoden in der Strömungsmesstechnik", 2014)
UnivIS-Import:2015-04-17:Pub.2014.tech.ITC.stmmec.unters